Decision Support System for Selection of Assembly Using Profile Matching Method and Simple Additive Weighting Method (Case Study: GKIN Diaspora Church) - Amesanggeng Pataropura; Riki Riki; Joshua Geraldo Manu (Komunitas Dosen Indonesia, 2019)
The church is a place of worship for Christians who are worshipers, in the church there are many organizers called the assemblies whose task is to regulate and manage all kinds of operational activities related to the worship held on Sundays, the duties and authorities of an assembly are in each position he has. To be a church administrator or assembly can be chosen by the congregation by conducting a selection process from the assemblies in the church and to be appointed by the pastor. The process of selecting the assembly can be an error to choose the assembly that can be subjective. Then a system for decision-making decision support is made using the Profile Matching Method and Simple Additive Weighting (SAW) Method. Where Profile matching is a decision support method using calculation of weight and weighting by dividing the main factors and supporting factors. And using the Simple Additive Weighting (SAW) method is a weighted housing method, by normalizing the decision decision matrix (x) to a scale that can be compared with all available alternative ratings